Complications from congenital Zika virus infection (Research, Society and Development, 2021)
Objective: To investigate in the national and international literature, the evidence about the complications resulting from the congenital Zika Virus infection. Methodology: This is an integrative literature review carried out in the databases: Cumulative Index to Nursing and Allied Health Literature (CINAHL), Medical Literature Analysis and Retrieval System Online (MEDLINE / PUBMED), Latin American and Caribbean Literature in Health Sciences (LILACS) and Web of Science (WoS), in February 2021. To define the inclusion criteria, the time frame from 2016 to 2020 was selected, original articles, available in full, free and online in the databases selected data and published in Portuguese, English and Spanish. Exclusion criteria were adopted: articles that were duplicated in the databases or articles in which it was not possible to identify a relationship with the theme by reading titles and abstracts. Results and discussion: From the searches in the databases and application of the eligibility criteria, 09 studies were included in the review, which after its analysis found that Zika Virus infection is considered a serious public health problem due to association with the increase in the apparent incidence of microcephaly in newborns of mothers infected by the virus, as well as other associated complications that can greatly affect the individual affected, such as: decreased brain volume, ventriculomegaly, cerebellar hypoplasia, lysencephaly with hydrocephalus and sequence deformation of akinesia, in addition to eye and hearing problems, joint contractures and dysphagia. Conclusion: From this perspective, there is a need for the formulation and implementation of measures to control the disease vector, considering each scenario, in order to prevent the transmission of this disease, especially to pregnant women, thus avoiding congenital transmission.